Metabolomics and databases driven approach of identification of phytochemicals from seed of Salvia schimperi using high-performance liquid chromatography tandem mass spectrometry - M. Azene; O. O. Olaokun; B.C. Iweriebor; N.M. Mkolo; C.L. Obi; W. Shibeshi; S. Assefa; Z. Abebe; A. Habtamu; K. Baye (PLoS ONE, 2025)
Salvia schimperi is widely used in Ethiopian folk medicine, particularly its raw and roasted seeds for treating ailments such as diarrhea. While numerous reports on its traditional uses and biological activities exist, limited chemical datasets are available on this plant. This study aimed to annotate and identify the phytochemical constituents in S. schimperi seed extracts. The ground samples of S. schimperi seeds (raw and roasted) were extracted with 80% methanol prior to metabolomic analysis using LCMS. Data processing and compound identification were conducted using MZmine, SIRIUS and XCMS platforms. Multivariate statistical analyses and biological targets prediction were carried out via XCMS, MetaboAnalyst, BindingDB and Therapeutic Target Databases. Annotation by SIRIUS based on ZODIAC, SIRIUS and confidence scores criteria, validated 99 of the 689 identified compounds. Among the compounds annotated by METLIN in XCMS, 105 were predicted to be of significant value based on multivariate analysis of MetaboAnalyst. Compounds annotated comprised of primary and secondary metabolites. Two alkaloid compounds (actinonin and indole acrylate) were identified as significant from SIRIUS and METLIN/MetaboAnalyst, with actinonin described as a potent antibacterial metabolite. To our knowledge, this study represents the first metabolomic fingerprinting of S. schimperi seed extracts, revealing diverse bioactive phytochemicals with nutritional and therapeutic potential. The consistent identification of actinonin suggests promising antibacterial applications. Roasting significantly alters the metabolite profile, reducing certain nutritional components such as isoleucine. These findings underline the importance of processing methods in determining phytochemical composition and bioactivity. Further research would explore the toxicity and potential functional food applications.